Effects of Antibiotic Therapy in Primary Sclerosing Cholangitis with and without Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis - Shah, Ayesha; Crawford, Darrel; Burger, Daniel; Martin, Neal; Walker, Marjorie; Talley, Nicholas J.; Tallis, Caroline; Jones, Michael; Stuart, Katherine; Keely, Simon; Lewindon, Peter; Macdonald, Graeme A.; Morrison, Mark; Holtmann, Gerald J. (Seminars in Liver Disease, 2019)
The authors conducted a systematic review and meta-analysis to assess the effect of antibiotic therapy in primary sclerosing cholangitis (PSC). Effect of antibiotic therapy on Mayo PSC Risk Score (MRS), serum alkaline phosphatase (ALP), total serum bilirubin (TSB), and adverse events (AEs) rates were calculated and expressed as standardized difference of means or proportions. Five studies including 124 PSC patients who received antibiotics were included. Overall, antibiotic treatment was associated with a statistically significant reduction in ALP, MRS, and TSB by 33.2, 36.1, and 28.8%, respectively. ALP reduction was greatest for vancomycin (65.6%, p < 0.002) and smallest with metronidazole (22.7%, p = 0.18). Overall, 8.9% (95% confidence interval: 3.9–13.9) of patients had AEs severe enough to discontinue antibiotic therapy. In PSC patients, antibiotic treatment results in a significant improvement in markers of cholestasis and MRS. Antibiotics, particularly vancomycin, may have a positive effect on PSC either via direct effects on the microbiome or via host-mediated mechanisms.
Keywords: vancomycin; antibiotics; primary sclerosing cholangitis; inflammatory bowel disease; ulcerative colitis; Crohn's disease; microbiome